2018
DOI: 10.1101/505214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing optogenetic stimulation protocols in auditory corticofugal neurons based on closed-loop spike feedback

Abstract: 2Optogenetics provides a means to probe functional connections between brain areas. By activating a set of presynaptic neurons and recording the activity from a downstream brain area, one 4 can establish the sign and strength of a feedforward connection. One challenge is that there are virtually limitless patterns that can be used to stimulate a presynaptic brain area. Functional influences on 6 downstream brain areas can depend not just on whether presynaptic neurons were activated, but how they were activate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In our study we were able to record from a larger neuronal population, revealing a subset of neurons in central IC that were modulated by feedback. This is consistent with another study which observed enhanced white noiseinduced activity in a small subset of neurons in the central nucleus of IC with activation of direct cortico-collicular feedback (Vila et al, 2019). The effects in central IC may be due to direct cortico-collicular feedback, intracollicular circuits (Saldaña and Merchań, 1992;Malmierca et al, 1995;Miller et al, 2005;Sturm et al, 2014) , or a combination of these mechanisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study we were able to record from a larger neuronal population, revealing a subset of neurons in central IC that were modulated by feedback. This is consistent with another study which observed enhanced white noiseinduced activity in a small subset of neurons in the central nucleus of IC with activation of direct cortico-collicular feedback (Vila et al, 2019). The effects in central IC may be due to direct cortico-collicular feedback, intracollicular circuits (Saldaña and Merchań, 1992;Malmierca et al, 1995;Miller et al, 2005;Sturm et al, 2014) , or a combination of these mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…Stimulation of AC had mixed effects on sound-evoked responses in IC, increasing and decreasing responses in different subpopulations of neurons (Jen et al, 1998;Zhou and Jen, 2005). Consistent with this effect, different patterns of direct corticocollicular activation enhanced or suppressed white noise-induced responses in IC (Vila et al, 2019). AC inactivation studies, on the other hand, found less consistent effects on IC responses.…”
Section: Introductionmentioning
confidence: 70%
“…The temporal profile of vS1 sensory responses was conserved under optogenetic excitation 21 . Figure 3c, left, shows the population peristimulus time histogram (PSTH) in EYFP-ChR2(H134R)-expressing rats in the absence of optogenetic excitation.…”
Section: Time Codingmentioning
confidence: 97%
“…These corticofugal projections likely play a major role in hearing by providing an anatomical substrate for "top-down" information to control early acoustic processing. Indeed, stimulating or silencing the auditory cortex in vivo changes spontaneous and sound-evoked activity throughout the central auditory system (Massopust and Ordy, 1962;Ryugo and Weinberger, 1976;Suga, 1998, 1999;Xiao and Suga, 2002;Yu et al, 2004;Nakamoto et al, 2008Nakamoto et al, , 2010Anderson and Malmierca, 2013;Kong et al, 2014;Vila et al, 2019;Blackwell et al, 2020;Qi et al, 2020), indicating that high-level activity regulates the moment-to-moment function of sub-cortical auditory circuits. However, little is known regarding the biophysical properties of auditory corticofugal synapses, nor do we understand how descending signals are integrated with ascending information.…”
Section: Introductionmentioning
confidence: 99%